A Study on the External Publicity Translation of Sichuan Baijiu Culture from the Perspective of Skopos Theory - Luo, Yuecen (Journal of Social Science and Humanities, 2026)
This paper systematically reviews the existing research progress on the external publicity translation of Sichuan Baijiu culture. It focuses on three core issues: the chaos in translating core terminologies, deviations in the translation of culturally loaded terms, and systemic translation failures in practical texts, thereby deeply analyzing the current practical dilemmas in the external publicity translation of Sichuan Baijiu culture. Guided by the theoretical framework of Skopos Theory, this paper proposes new strategies centered on text type adaptation, standardization of professional terminologies, and in-depth translation of cultural keywords. Based on that, it further explores specific paths to enhance the effectiveness of external publicity translation through optimizing the construction of external publicity websites for Sichuan Baijiu enterprises and establishing a collaborative mechanism involving “translation experts, cultural consultants, and industry mentors.” These efforts aim to provide theoretical support and practical references for the deepening of subsequent research and the practical application of translation in Sichuan Baijiu culture.